(untitled) (One Health & Risk Management, 2021)
Introduction. Over the last 15 years, the occupational mortality rate has considerably increased among health care workers from the Republic of Moldova. The major risk factors determining the morbidity and mortality rates among medical staff include physical, chemical, biological and psycho-social factors. The most common occupational diseases occurring among healthcare providers are due to non-compliance to occupational safety and hygiene guidelines, personal hygiene, sanitary- epidemiological regulations, violation of protection norms and inadequate endowment of sanitary and social rooms, as well as of individual protective means. Workplace stress is a universal issue, the most common being the occupational burnout syndrome, characterized by physical, mental and emotional exhaustion. Material and methods. The research was conducted on 75 medical workers during the years 2020-2021, 80% of which were women and 20% - men. 80% of the studied people were aged between 20-30 years old. To assess the risk factors, a questionnaire was developed, which included 26 questions divided into several compartments. Results. 51 nurses, 13 paramedics, 8 doctors and 3 auxiliary medical staff were surveyed. 91% of participants claimed that their job is associated with health risks, whereas 9% respondents disagreed upon that statement. At workplace, the medical staff complained of fatigue in 86.7% of cases, stress – 65.3%, anxiety – 26.7%, and discomfort – 17.3%. The most commonly encountered physical factors were reported to be the noise – 56%, unfavorable microclimate – 52%, inadequate lighting – 41.3%, vibrations – 25.3%, ionizing radiation – 12%, non-ionizing radiation - 5.3% and 12% respondents denied any physical factors. The most common chemical factors were as following: disinfectants – 89.3%, antiseptics – 80%, drugs – 65.3%, latex – 50.7%, laboratory reagents – 8%, anesthetic gases – 8% and 6.7% denied the presence of any chemical factors. The reported biological factors included viruses – 77.3%, bacteria – 73.3%, antibiotics – 42.7%, fungi – 41.3%, parasites - 40%, vaccines and serum – 17, 3%, whereas 9.3% encountered no chemical factors at their workplace. The psychosocial factors were most frequently reported at workplace, being as follows: overtime work – 74.7%, talking to patients - 54.7%, employer-employee relationship – 44%, collegial relationship – 38.7% and 6.7% did not encounter such problems. The commonest workplace challenges were as follows: poor body posture - 62.7%, weightlifting or patient transporting – 48%, long-lasting orthostatic position – 34.7%, long-lasting sitting position - 18.7%, and 8% did not claim any of such problems. The overall health condition of the respondents after a day of work was assessed as satisfactory – 57.3%, unsatisfactory – 22.7%, good – 16%, very good – in only 4% of participants. Working conditions were considered as satisfactory and affecting the work capacity and health in 78.7% of cases, unfavorable or life-threatening -13.3%, favorable or not affecting the work capacity and well-being in – 8% of respondents. Conclusions. The healthcare workers activity is accompanied by the presence of certain risk factors, which might lead to the development of occupational diseases.